2014
DOI: 10.3389/fnins.2014.00258
|View full text |Cite
|
Sign up to set email alerts
|

Relating resting-state fMRI and EEG whole-brain connectomes across frequency bands

Abstract: Whole brain functional connectomes hold promise for understanding human brain activity across a range of cognitive, developmental and pathological states. So called resting-state (rs) functional MRI studies have contributed to the brain being considered at a macroscopic scale as a set of interacting regions. Interactions are defined as correlation-based signal measurements driven by blood oxygenation level dependent (BOLD) contrast. Understanding the neurophysiological basis of these measurements is important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 67 publications
9
131
0
Order By: Relevance
“…The results show that both anodal and cathodal stimulation affected mainly the low (theta and alpha) frequency EEG bands, modulating specific cortical connections in intra-and interhemispheric networks. Considering that the resting state patterns of brain connectivity are the result of robust and specific intrinsic neural activity (Cabral et al, 2014;Deligianni et al, 2014), our results highlight that tDCS is able to affect selectively the spontaneous neuronal fluctuations, modulating the dynamics of the brain at rest. Although tDCS is able to change network properties, it doesn't seem to affect the topological organization of the brain activity at a global level.…”
Section: Discussionmentioning
confidence: 93%
“…The results show that both anodal and cathodal stimulation affected mainly the low (theta and alpha) frequency EEG bands, modulating specific cortical connections in intra-and interhemispheric networks. Considering that the resting state patterns of brain connectivity are the result of robust and specific intrinsic neural activity (Cabral et al, 2014;Deligianni et al, 2014), our results highlight that tDCS is able to affect selectively the spontaneous neuronal fluctuations, modulating the dynamics of the brain at rest. Although tDCS is able to change network properties, it doesn't seem to affect the topological organization of the brain activity at a global level.…”
Section: Discussionmentioning
confidence: 93%
“…Neuroimaging studies often use low-rank multi-output models like CCA (Hotelling, 1936) and partial least squares (PLS) (Krishnan et al, 2011) to link imaging based features to other 115 blocks of data: to cross-predict fMRI and EEG (Deligianni et al, 2014), to explain genetic outcomes (Floch et al, 2012), behavioral and clinical scores (Monteiro et al, 2016;Miller et al, 2016;Smith et al, 2015), or a different imaging modality (Avants et al, 2010;Sui et al, 2012). Reduced rank regression 120 (Vounou et al, 2010;Izenman, 1975) is a related multi-output linear-regression.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, we observed that partial covariance estimates were more reliable than full covariance estimates both at the individual and group level. This work adds to previous studies which have applied Ledoit-Wolf shrinkage to calculate partial correlation values (Varoquaux et al, 2012, Deligianni et al, 2014). …”
Section: Discussionmentioning
confidence: 84%
“…Covariance matrix shrinkage has been recently used in the investigation of functional connectivity (Varoquaux et al, 2012, Deligianni et al, 2014, Shou et al, 2014). Stein’s paradox (Stein, 1956) asserts that a shrunken estimate of the mean outperforms the sample mean in predicting the true mean of a multivariate distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation